Masterbatch, resin composition, and resin molded product
Patent Information
- Application Number
- JP2024163242
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-09-20
Smart Images

Figure 0007644301000001 
Figure 0007644301000002 
Figure 0007644301000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a masterbatch, a resin composition, and a resin molded article. [Background technology]
[0002] Polyester resins are currently used in various fields such as PET bottles, sheets, films, and fibers. For example, in recent years, the use of PET bottles, mainly for beverages, has become remarkable, and the amount of PET bottles used has become enormous. In Japan, colorless and transparent PET bottles are used to promote recycling. In recent years, there has been an increasing social demand for recycling resources by reusing products that are produced and consumed in large quantities, rather than simply disposing of the waste after consumption. Under such circumstances, recycling of PET bottles in particular has progressed.
[0003] There are various methods for recycling PET bottles. Material recycling includes horizontal recycling and cascade recycling. Horizontal recycling is a method in which used PET bottles are collected, crushed, and washed to produce recycled polyethylene terephthalate flakes, which are then used as raw material to manufacture PET bottles again. On the other hand, cascade recycling is a recycling method in which the recycled polyethylene terephthalate flakes are then used to produce products with lower performance requirements than PET bottles, such as films and fibers. In either case, there is a limit to the number of times the material can be recycled, as the polyethylene terephthalate is broken down into smaller molecules due to heat history and other factors with each recycling process, causing deterioration in moldability and strength.
[0004] As one of the methods for obtaining a product with improved quality from flakes of low molecular weight recycled polyethylene terephthalate, a method of blending an effective chain extender with polyester resin and melt-kneading has been proposed. For example, Patent Document 1 discloses a modifier for crystalline polyester resin, which contains an amorphous polyester resin and a reactive compound containing two or more glycidyl groups and / or isocyanate groups per molecule and having a weight average molecular weight of 200 to 500,000. This modifier is said to be capable of improving the moldability in melt molding of crystalline polyester resin, particularly PET flakes recycled from used polyethylene terephthalate bottles, and improving mechanical properties while maintaining transparency.
[0005] Patent Document 2 discloses a masterbatch for chain extension of polyester resin, which contains a predetermined polyester resin (A), an epoxy group-containing resin (B) having a weight average molecular weight of 6000 to 200000, and a chain-extended polyester resin (C) which is a reaction product of the polyester resin (A) and the resin (B). According to Patent Document 2, the contents of the resin (B) and the chain-extended polyester resin (C) in the masterbatch are set within a predetermined range, and the epoxy value of the resin (B) is set within a predetermined range. It is said that this makes it possible to provide a method for producing a polyester resin molded body that is excellent in moldability and can improve the quality of the molded body by a general-purpose processing method, and a masterbatch for use in the manufacturing method. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2006-45477 A [Patent Document 2] International Publication No. 2023 / 153522 Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the techniques disclosed in the above-mentioned Patent Documents 1 and 2, it is understood that the transparency of the molded product is improved or maintained by the type and ratio of monomer components such as diol (glycol) components constituting the polyester resin used. A technique is required that can obtain a resin composition with good transparency by mixing with a polyester resin to be modified or chain extended, such as in the form of a modifier or a masterbatch for chain extension.
[0008] Therefore, the present invention aims to provide a masterbatch for a polyester resin, which has good processability and moldability when diluted with a polyester resin, and is capable of obtaining a resin composition having good transparency and low yellowness. [Means for solving the problem]
[0009] That is, according to the present invention, there is provided a masterbatch for a polyester resin, which contains amorphous polyethylene terephthalate (A) and a chain extender (B) having a weight-average epoxy functional group number of 3 or more and 65 or less and a weight-average molecular weight of 2,000 or more and 30,000 or less, and which satisfies the following conditions (1) to (3): Condition (1): The content of the chain extender (B) in the master batch is 5% by mass or more and 30% by mass or less based on the total mass of the master batch. Condition (2): Intrinsic viscosity IV after melt kneading alone a The intrinsic viscosity of a resin composition sample obtained by melt-kneading a crystalline polyethylene terephthalate having a viscosity of 0.9 dL / g or more and 1.0 dL / g or less with the master batch in a ratio such that the content of the chain extender (B) is 0.4 mass % is expressed as IV b (dL / g), 0 <IV b -IV a <0.29. Condition (3): The masterbatch is mixed with the polyester resin under conditions in which the content of the chain extender (B) in a resin composition containing the masterbatch and the polyester resin is 0.01 mass % or more and 1.0 mass % or less. Effect of the Invention
[0010] According to the present invention, it is possible to provide a masterbatch for a polyester resin, which, when diluted with a polyester resin, has good processability and moldability, and is capable of obtaining a resin composition having good transparency and low yellowness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.
[0012] <Master batch> A masterbatch according to one embodiment of the present invention (hereinafter, sometimes simply referred to as "masterbatch") is a masterbatch for polyester resin. In the present disclosure, the polyester resin for which the masterbatch is used may be referred to as "polyester resin (C)". In addition, since the masterbatch contains amorphous polyethylene terephthalate (A), it is a type of resin composition. For convenience, in the present disclosure, a composition obtained by mixing the masterbatch and the polyester resin (C) by melt kneading or the like and a composition to be compared therewith are referred to as "resin composition". Furthermore, in the present disclosure, a molded body obtained by molding the resin composition by a method such as injection molding is referred to as "resin molded body".
[0013] The masterbatch contains amorphous polyethylene terephthalate (A) and a chain extender (B). The chain extender (B) has a weight average number of epoxy functional groups of 3 or more and 65 or less, and a weight average molecular weight of 2000 or more and 30000 or less. The masterbatch satisfies the following conditions (1) to (3).
[0014] Condition (1): The content of the chain extender (B) in the masterbatch is 5% by mass or more and 30% by mass or less, based on the total mass of the masterbatch.
[0015] Condition (2): Intrinsic viscosity IV after melt kneading alone a The intrinsic viscosity of a resin composition sample obtained by melt-kneading a crystalline polyethylene terephthalate having a viscosity of 0.9 dL / g or more and 1.0 dL / g or less and a master batch in a ratio such that the content of the chain extender (B) is 0.4 mass % is measured by IV b (dL / g), 0 <IV b -IV a <0.29.
[0016] Condition (3): The masterbatch is mixed with the polyester resin (C) under the condition that the content of the chain extender (B) in the resin composition containing the masterbatch and the polyester resin (C) is 0.01 mass% or more and 1.0 mass% or less.
[0017] By using a master batch containing the amorphous polyethylene terephthalate (A) and the specific chain extender (B) and satisfying all of the conditions (1) to (3), it is possible to obtain a target resin composition. That is, when the master batch is diluted with the polyester resin (C), it is possible to obtain a resin composition that has good processability and moldability, is less likely to become cloudy, has good transparency, and has low yellowness.
[0018] Each component of the masterbatch and the conditions (1) to (3) will be described in detail below.
[0019] (Amorphous polyethylene terephthalate (A)) The masterbatch contains amorphous polyethylene terephthalate (A) (hereinafter, sometimes referred to as "amorphous PET (A)"). Amorphous PET (A) is the base resin in the masterbatch. By using amorphous PET (A) as the base resin in the masterbatch, the crystallization temperature of the polyester resin (C) can be lowered when the masterbatch is diluted with the polyester resin (C). This can contribute to providing a resin composition with good processability, moldability, and transparency.
[0020] On the other hand, if crystalline polyethylene terephthalate (hereinafter sometimes referred to as "crystalline PET") is used as the base resin of the masterbatch instead of amorphous PET (A), it may be difficult to manufacture the masterbatch. This is because, coupled with the fact that the processing temperature of crystalline PET is higher than that of amorphous PET, the crosslinking reaction between the crystalline PET and the chain extender (B) is accelerated during the masterbatch manufacturing stage, which may result in gelation.
[0021] Polyethylene terephthalate can be synthesized by dehydration condensation of ethylene glycol and terephthalic acid, or by transesterification of ethylene glycol and dimethyl terephthalate. Amorphous PET (A) is polyethylene terephthalate (PET) that does not have a crystallization temperature, and is known as "A-PET" (abbreviation for amorphous polyethylene terephthalate) or "PET-G" (abbreviation for glycol-modified polyethylene terephthalate). PET-G is an amorphous PET in which a portion of the ethylene glycol units in PET (for example, about 30 to 40 mol%) are replaced with cyclohexanedimethanol units.
[0022] Among the amorphous PET (A), glycol-modified polyethylene terephthalate (PET-G) is preferred. By using PET-G, the crystallization temperature of the diluent polyester resin (C) can be more easily lowered, which contributes to providing a resin composition with better processability, moldability, and transparency.
[0023] The crystallinity and amorphousness of a thermoplastic resin can be determined by the presence or absence of an exothermic peak associated with crystallization when the target thermoplastic resin is heated from 30°C to 300°C at 10°C / min in differential scanning calorimetry (DSC), melted, and then cooled to 30°C at 10°C / min to solidify. Specifically, when the exothermic peak is observed, the thermoplastic resin can be determined to be crystalline. When the exothermic peak is not observed, the thermoplastic resin can be determined to be amorphous. Therefore, as the amorphous PET (A), an amorphous PET (A) can be used that does not observe an exothermic peak associated with crystallization when the target thermoplastic resin is heated from 30°C to 300°C at 10°C / min in differential scanning calorimetry, melted, and then cooled to 30°C at 10°C / min to solidify. A differential scanning calorimeter (DSC) is used to observe the exothermic peak.
[0024] As the amorphous PET (A), a commercially available product can be used. Examples of commercially available products of the amorphous PET (A) include the "EASTAR" series manufactured by Eastman Chemical Company and the "SKYGREEN" series manufactured by SK Chemical Company. The amorphous PET (A) may be used alone or in combination of two or more types.
[0025] The content of amorphous PET (A) in the masterbatch is preferably 70% by mass or more and 95% by mass or less, more preferably 72% by mass or more and 92% by mass or less, and even more preferably 75% by mass or more and 90% by mass or less, based on the total mass of the masterbatch. When the content of amorphous PET (A) in the masterbatch is within the above range, a resin composition having better processability, moldability, and transparency and lower yellowness is easily obtained when the masterbatch is diluted with polyester resin (C).
[0026] (Chain extender (B)) The master batch contains a chain extender (B). This chain extender (B) has a weight average epoxy functional group number of 3 to 65 and a weight average molecular weight of 2000 to 30000. Since the chain extender (B) has a weight average epoxy functional group number of 3 to 65, it has a glycidyl group (epoxy group). The glycidyl group of the chain extender (B) can react with at least one of a hydroxy group and a carboxy group (hereinafter, sometimes referred to as a "hydroxy group and / or a carboxy group") of the polyester resin (C). Therefore, when the master batch is diluted with the polyester resin (C), the chain extender (B) reacts with the polyester resin (C) to extend the chain of the polyester resin (C) and increase the molecular weight, thereby making it possible to suppress deformation during molding while suppressing yellowing and clouding.
[0027] The weight-average epoxy functional group number and weight-average molecular weight of the chain extender (B) must both be within the above-mentioned specific ranges. The weight-average epoxy functional group number of the chain extender (B) is preferably 3 to 65, and the weight-average molecular weight of the chain extender (B) is preferably 4,000 to 20,000, more preferably 7,000 to 12,000.
[0028] If the weight-average epoxy functional group number of the chain extender (B) is 3 or more and 65 or less, or more than 65, and the weight-average molecular weight is less than 2000, an excessive crosslinking reaction is likely to occur between the chain extender (B) and the polyester resin (C) in the masterbatch. Therefore, the resin composition obtained by diluting with the polyester resin (C) is likely to be whitened and have poor transparency. Furthermore, the viscosity increases during melt-kneading of the masterbatch and the polyester resin (C), and the dispersion of the chain extender (B) in the polyester resin (C) may be insufficient. On the other hand, if the weight-average epoxy functional group number of the chain extender (B) is 3 or more and 65 or less, or less than 3, and the weight-average molecular weight is more than 30000, the above crosslinking reaction is unlikely to occur sufficiently, and the resulting resin composition may have poor moldability. Furthermore, if the weight-average epoxy functional group number of the chain extender (B) is less than 3, and the weight-average molecular weight is less than 2000, the above crosslinking reaction is insufficient, and the resulting resin composition may have poor processability and moldability. On the other hand, if the weight average number of epoxy functional groups of the chain extender (B) exceeds 65 and the weight average molecular weight exceeds 30,000, the above-mentioned crosslinking reaction is more likely to occur excessively, and the resin composition obtained by diluting with the polyester resin (C) tends to whiten and have poor transparency.
[0029] In the present disclosure, the weight average molecular weight of the chain extender (B) refers to a value measured in terms of polystyrene by gel permeation chromatography (GPC). Specifically, the weight average molecular weight of the chain extender (B) can be a value measured by the following apparatus and conditions. GPC equipment: Product name "HLC-8020" (manufactured by Tosoh Corporation) Column: Product name "TSKgel G2000HXL", "G3000HXL", "G4000GXL" (manufactured by Tosoh Corporation) Solvent: Tetrahydrofuran (THF) ·Flow rate: 1.0mL / min Sample concentration: 2g / L ·Injection volume: 100μL ·Temperature: 40℃ Detector: Model number "RI-8020" (Tosoh Corporation) Standard material: TSK standard polystyrene (manufactured by Tosoh Corporation)
[0030] As described above, the chain extender (B) has a glycidyl group (epoxy group), which is a functional group capable of reacting with a hydroxyl group and / or a carboxyl group of the polyester resin (C). The average number of glycidyl groups (epoxy groups) per molecule of the chain extender (B) is expressed as the weight average epoxy functional group number, and can be appropriately set according to the desired strength of reaction. The weight average epoxy functional group number can be calculated by the weight average molecular weight / epoxy equivalent of the chain extender (B). For example, by determining the target weight average molecular weight, the ratio of a polymerizable monomer having a glycidyl group (epoxy group) to another polymerizable monomer is adjusted and polymerized. Thereby, a chain extender (B) having a desired average number of glycidyl groups (epoxy groups) per molecule can be produced.
[0031] As an example, the case of producing a chain extender (B) using glycidyl methacrylate as a polymerizable monomer having a glycidyl group and styrene as another polymerizable monomer will be described. Specifically, the case of producing a chain extender (B) having a weight average molecular weight of 5000 and an average number of glycidyl groups (epoxy groups) per molecule of 4 using styrene and glycidyl methacrylate is as follows. By charging styrene (molecular weight 104.15) and glycidyl methacrylate (molecular weight 142.15) in a styrene:glycidyl methacrylate = 10.6: 1 (mass ratio), a styrene / glycidyl methacrylate copolymer can be obtained as the target chain extender (B).
[0032] The weight-average number of epoxy functional groups in the chain extender (B) is 3 or more and 65 or less, and preferably 4 or more and 50 or less. Due to the effect of the chain extender (B), when the master batch and the polyester resin (C) are melt-kneaded, the hydroxyl group and / or carboxyl group of the polyester resin (C) react with the chain extender (B) and are partially crosslinked. This improves the strength during melt-kneading, and makes it easier to obtain a resin composition with good moldability.
[0033] If the weight average molecular weight of the chain extender (B) is 2000 to 30000 or more, or more than 30000, and the weight average epoxy functional group number is less than 3, the number of crosslinking points between the chain extender (B) and the polyester resin (C) in the masterbatch is reduced. Therefore, the strength improvement during melt-kneading of the masterbatch and the polyester resin (C) is insufficient, and the moldability of the resulting resin composition may be reduced. On the other hand, if the weight average molecular weight of the chain extender (B) is 2000 to 30000 or less, or less than 2000, and the weight average epoxy functional group number is more than 65, the above-mentioned crosslinking points are too many, and the reaction between the chain extender (B) and the polyester resin (C) proceeds. Therefore, the resulting resin composition may be whitened and have poor transparency, and the reaction with the polyester resin (C) may occur too much, and the resulting resin composition may have poor moldability. If the weight-average molecular weight of the chain extender (B) is less than 2000 and the weight-average epoxy functional group number is less than 3, the above crosslinking reaction may be insufficient, and the resulting resin composition may have poor processability and moldability. On the other hand, if the weight-average molecular weight of the chain extender (B) is more than 30000 and the weight-average epoxy functional group number is more than 65, the above crosslinking reaction is more likely to occur excessively, and the resin composition obtained by diluting with the polyester resin (C) may whiten and have poor transparency.
[0034] The epoxy equivalent of the chain extender (B) is preferably 100 g / mol or more and 1000 g / mol or less, more preferably 150 g / mol or more and 800 g / mol or less, and even more preferably 200 g / mol or more and 600 g / mol or less. When the epoxy equivalent of the chain extender (B) is 100 g / mol or more, the above-mentioned crosslinking points are appropriately increased, and the strength during melt-kneading of the master batch and the polyester resin (C) is easily improved, and the moldability of the obtained resin composition is easily improved. On the other hand, when the epoxy equivalent of the chain extender (B) is 1000 g / mol or less, the above-mentioned crosslinking points are suppressed to an appropriate amount, and the transparency of the obtained resin composition is easily improved. In the present disclosure, the epoxy equivalent of the chain extender (B) can be a value measured in accordance with the provisions of JIS K7236.
[0035] The chain extender (B) may have a glycidyl group (epoxy group) in the main chain, side chain, or terminal of the molecular chain, or may have a plurality of them. The type of the chain extender (B) is not particularly limited as long as the weight average epoxy functional group number and the weight average molecular weight are both within the above-mentioned specific ranges. As described above, a suitable chain extender (B) may be a copolymer of a monomer mixture containing a polymerizable monomer having a glycidyl group (epoxy group) and another polymerizable monomer. The copolymer may be any of a random copolymer, a block copolymer, a graft copolymer, and an alternating copolymer.
[0036] Suitable examples of polymerizable monomers having a glycidyl group include (meth)acrylate monomers having a glycidyl group (hereinafter, may be referred to as "glycidyl (meth)acrylate monomers"). Examples of glycidyl (meth)acrylate monomers include glycidyl acrylate, glycidyl methacrylate, 4-hydroxybutyl acrylate glycidyl ether, and allyl glycidyl ether. One or more of these can be used. Among these, glycidyl acrylate and glycidyl methacrylate are preferred. In the present disclosure, the term "(meth)acrylate" means that both "acrylate" and "methacrylate" are included.
[0037] Other suitable examples of polymerizable monomers include styrene-based monomers, (meth)acrylate-based monomers, and olefin-based monomers. Examples of styrene-based monomers include styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, vinylxylene, ethylstyrene, dimethylstyrene, and p-tert-butylstyrene. One or more types of styrene-based monomers can be used. Examples of (meth)acrylate-based monomers include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, and ethylhexyl (meth)acrylate. One or more types of (meth)acrylate-based monomers can be used. Examples of olefin-based monomers include ethylene, propylene, butadiene, and isoprene. One or more types of olefin-based monomers can be used.
[0038] Preferred types of chain extender (B) include copolymers of a styrene-based monomer and a glycidyl (meth)acrylate-based monomer (styrene / glycidyl (meth)acrylate-based copolymer), copolymers of a styrene-based monomer, a (meth)acrylate-based monomer and a glycidyl (meth)acrylate-based monomer (styrene / (meth)acrylate / glycidyl (meth)acrylate-based copolymer), and copolymers of a styrene-based monomer, an olefin-based monomer and a glycidyl (meth)acrylate-based monomer (styrene / olefin / glycidyl (meth)acrylate-based copolymer).
[0039] As the chain extender (B), a commercially available product can be used. Examples of commercially available chain extenders (B) include the "Joncryl" ADR series manufactured by BASF, the "Alphon" series manufactured by Toagosei Co., Ltd., the "Marproof" series manufactured by NOF Corp., the "Bondfast" series manufactured by Sumitomo Chemical Co., Ltd., and the "Rotader" series manufactured by SK Chemical Co., Ltd. The chain extender (B) may be used alone or in combination of two or more types.
[0040] [Condition (1)] The masterbatch satisfies the above condition (1) with respect to the content of the chain extender (B) in the masterbatch. That is, the content of the chain extender (B) in the masterbatch is 5% by mass or more and 30% by mass or less based on the total mass of the masterbatch. The content of the chain extender (B) in the masterbatch is preferably 8% by mass or more and 28% by mass or less, and more preferably 10% by mass or more and 25% by mass or less, based on the total mass of the masterbatch. When the content of the chain extender (B) in the masterbatch is within the above range, a resin composition having better processability, moldability, and transparency is easily obtained when the masterbatch is diluted with the polyester resin (C).
[0041] If the content of the chain extender (B) in the masterbatch is less than 5% by mass, the masterbatch is likely to gel when the amorphous PET (A) and the chain extender (B) are melt-kneaded to produce the masterbatch, making it difficult to produce the masterbatch. Even if the masterbatch can be produced, the heat resistance of the polyester resin (C) is likely to decrease when the masterbatch is diluted with the polyester resin (C). On the other hand, if the content of the chain extender (B) in the masterbatch is more than 30% by mass, the proportion of the amorphous PET (A) in the masterbatch decreases, so that mechanical properties such as impact resistance tend to decrease, and the transparency of the resin composition obtained by diluting the masterbatch with the polyester resin (C) tends to decrease. Furthermore, if the content of the chain extender (B) in the masterbatch is high, the amorphous PET (A) and the chain extender (B) are unlikely to be mixed uniformly when the amorphous PET (A) and the chain extender (B) are melt-kneaded to produce the masterbatch. Specifically, the chain extender (B) comes out in liquid form on the surface of the mixture during the production process of the masterbatch, and the mixture is difficult to solidify, making it difficult to produce the masterbatch.
[0042] [Condition (2)] In order to obtain the desired resin composition when the masterbatch is diluted with a polyester resin, the condition (2) is also necessary as described above. That is, the intrinsic viscosity IV aThe intrinsic viscosity of a resin composition sample obtained by melt-kneading a crystalline PET having a viscosity of 0.9 dL / g or more and 1.0 dL / g or less with a master batch in a ratio such that the content of the chain extender (B) is 0.4 mass % is IV b (dL / g), 0 <IV b -IV a The crystalline PET under condition (2) can be used as the polyester resin (C), and has an intrinsic viscosity IV b The resin composition sample is used as a raw material for measuring the intrinsic viscosity IV of crystalline PET. a Regarding the intrinsic viscosity, IV a Intrinsic viscosity is the volume per unit mass that a polymer occupies in a solution (unit: dL / g), depends on the molecular weight of the polymer, and is used as a measure of molecular weight.
[0043] From the above condition (2), the intrinsic viscosity IV b is the intrinsic viscosity IV of the resin obtained by melt-kneading the above crystalline PET alone. a Greater than (IV b >IV a ). If IV b =IV a If so, then IV b -IV a = 0, which means that the intrinsic viscosity is the same regardless of whether or not the masterbatch is added to the crystalline PET. Therefore, in this case, even if the masterbatch is added to the polyester resin (C), no improvement in moldability can be expected. In addition, if IV b <IV a If so, then IV b -IV a <0, which means that even if the masterbatch is added to the above crystalline PET, the intrinsic viscosity is reduced. Therefore, in this case, the effect of adding the masterbatch to the polyester resin (C) is outweighed by the effect of hydrolysis during processing, and the moldability is reduced. Furthermore, IV b-IV a If the viscosity is 0.29 dL / g or more, the moldability is likely to decrease, and the resin composition is likely to become cloudy or have a high yellow color and thus have poor transparency.
[0044] As mentioned above, IV b and IV a Difference (IV b -IV a ) is greater than 0 dL / g and less than 0.29 dL / g. IV b -IV a Regarding the value of , the larger the value is near the lower limit (a value exceeding 0 and near 0), the easier it is to improve moldability. On the other hand, near the upper limit (a value less than 0.29 and near 0.29), the smaller the value is, the easier it is to improve transparency and reduce yellowness. IV b and IV a Difference (IV b -IV a ) is 0.05dL / g or more and 0.25dL / g or less (0.05≦IV b -IV a ≦0.25). b -IV a When the value is in the above preferred range, a resin composition having better processability and moldability, as well as better transparency and lower yellowness can be easily obtained.
[0045] In addition, the intrinsic viscosity IV a In order to select a crystalline PET having an intrinsic viscosity of 0.9 dL / g or more and 1.0 dL / g or less, it is advisable to select a crystalline PET having an intrinsic viscosity of 1.1 dL / g or more and 1.3 dL / g or less before being melt-kneaded alone.
[0046] In the present disclosure, the intrinsic viscosity (IV) is a value (dL / g) measured at 25°C according to the method specified in JIS K7367-5, using a mixed solvent of phenol and 1,1,2,2-tetrachloroethane (tetrachloroethane) in a mass ratio of 1:1 as the solvent and an Ostwald viscosity tube as the measuring device.
[0047] [Condition (3)] In order to obtain the desired resin composition when the masterbatch is diluted with a polyester resin, the condition (3) is also necessary as described above. That is, the masterbatch needs to be mixed with the polyester resin (C) under conditions in which the content of the chain extender (B) in the resin composition containing the masterbatch and the polyester resin (C) is 0.01% by mass or more and 1.0% by mass or less.
[0048] From the viewpoint of improving the moldability of the resin composition, the content of the chain extender (B) in the resin composition under condition (3) is preferably 0.02% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more. On the other hand, from the viewpoint of improving the transparency of the resin composition, the content of the chain extender (B) in the resin composition under condition (3) is preferably 0.9% by mass or less, more preferably 0.7% by mass or less, and even more preferably 0.5% by mass or less.
[0049] (Polyester resin (C)) The polyester resin (C) is a resin used to dilute the masterbatch, and is a resin that constitutes a resin composition together with the masterbatch by being mixed with the masterbatch. The polyester resin (C) is usually a resin having a constitutional unit derived from an aromatic dicarboxylic acid and a constitutional unit derived from an alkylene diol.
[0050] Examples of the polyester resin (C) include polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT), polybutylene terephthalate (PBT), polycyclohexylene dimethylene terephthalate (PCT), polyethylene naphthalate (PEN), polybutylene naphthalate (PBN), polylactic acid (PLA), polyethylene terephthalate-isophthalate resin (I-PET), and polycarbonate (PC). In addition, polyester resins in which a part of these resins has been replaced, such as glycol-modified polyethylene terephthalate (PET-G), or polyester resins regenerated by chemical recycling (chemical regeneration method) or mechanical recycling (physical regeneration method) may be used. The polyester resin (C) may be used alone or in combination of two or more kinds.
[0051] As the polyester resin (C), both crystalline polyester resin and amorphous polyester resin can be used. Among these, it is preferable to use a crystalline polyester resin because the above-mentioned master batch has a high effect of improving moldability. Among them, crystalline polyethylene terephthalate, crystalline polytrimethylene terephthalate, crystalline polybutylene terephthalate, crystalline polycyclohexylene dimethylene terephthalate, crystalline polylactic acid, crystalline polyethylene terephthalate-isophthalate, and crystalline polycarbonate are more preferable. Therefore, it is more preferable that the polyester resin (C) contains at least one selected from the group consisting of crystalline polyethylene terephthalate, crystalline polytrimethylene terephthalate, crystalline polybutylene terephthalate, crystalline polycyclohexylene dimethylene terephthalate, crystalline polylactic acid, crystalline polyethylene terephthalate-isophthalate, and crystalline polycarbonate.
[0052] As the polyester resin (C), commercially available products may be used. Examples of commercially available PET products include the "Kurapet" series and "Bio-Kurapet" series manufactured by Kuraray Co., Ltd., the "Unitika Polyester" series manufactured by Unitika Co., Ltd., and the "SKYPET" series manufactured by SK Chemical Co., Ltd. Examples of commercially available PTT products include the "Solona" series manufactured by DuPont Co., Ltd. Examples of commercially available PBT products include the "Trecon" series manufactured by Toray Co., Ltd., the "NovaDuran" series manufactured by Mitsubishi Chemical Co., Ltd., and the "Duranex" series manufactured by Polyplastics Co., Ltd. Examples of commercially available PCT products include the "SKYPURA" series manufactured by SK Chemical Co., Ltd. Examples of commercially available PEN products include the "Teonex" series manufactured by Teijin Co., Ltd. Examples of commercially available polylactic acid products include the "Terramac" series manufactured by Unitika Co., Ltd. Commercially available I-PET products include the "Bellpet" series manufactured by Bell Polyester Products Co., Ltd. Commercially available PC products include the "Panlite" series manufactured by Teijin Limited.
[0053] (Other Ingredients) The master batch may contain other components as necessary in addition to the above-mentioned amorphous PET (A) and chain extender (B). Examples of other components include pigments, fillers, surface treatment agents, lubricants, plasticizers, crosslinking agents, UV absorbers, light stabilizers, antioxidants, antistatic agents, antibacterial agents, flame retardants, and foaming agents. One type of other component may be used alone, or two or more types may be used in combination.
[0054] <Masterbatch manufacturing method> The master batch can be produced by melt-kneading a material containing the amorphous polyethylene terephthalate (A) and the chain extender (B). During this melt-kneading, the above-mentioned other components may be added as necessary.
[0055] As a method of melt kneading when obtaining a masterbatch, for example, a method of premixing materials containing amorphous PET (A) and a chain extender (B) using a mixer such as a high-speed mixer such as a Henschel mixer or a tumbler, and then melt kneading using a kneading device can be mentioned. Examples of the kneading device include a Banbury mixer, a roll, a plastograph, a single-screw extruder, a twin-screw extruder, a kneader, and a pressure kneader. The above materials are melt kneaded using a kneading device such as an extruder, and the kneaded material is extruded into a strand shape, and the kneaded material extruded into a strand shape may be processed into a pellet shape, flake shape, or other shape. As long as it can be melt kneaded, the kneading device to be used is not particularly limited, but a pressure kneader, a Banbury mixer, or a twin-screw extruder is preferably used because of its high kneading ability. In addition, from the viewpoint of ease of use of the masterbatch when obtaining a resin composition, it is preferable that the masterbatch is processed as described above and has a pellet or flake shape.
[0056] The temperature during melt kneading when obtaining the master batch may be any temperature at which the thermoplastic resin containing the amorphous PET (A) melts, and is preferably 200°C or more and 260°C or less, and more preferably 220°C or more and 240°C or less. The melt kneading when obtaining the master batch may be performed in one stage or two stages. In the two-stage melt kneading, for example, a part of the amorphous PET (A) and the chain extender (B) are melt kneaded, and the kneaded product extruded in a strand shape is processed into a pellet or flake shape. Next, the remaining amorphous PET (A) and the chain extender (B), as well as other components as necessary, are added to the kneaded product in the pellet or flake shape, and the kneaded product is melt kneaded again.
[0057] As described above in detail, the master batch of this embodiment contains amorphous PET (A) and a specific chain extender (B), and satisfies all of the above-mentioned conditions (1) to (3). Therefore, when this master batch is diluted with polyester resin (C), it is possible to obtain a resin composition that has good processability and moldability, is less likely to become cloudy, has good transparency, and has low yellowness. In this way, the effect of the master batch is realized by mixing (melting and kneading) the master batch with the polyester resin (C) that is the diluting resin. If the amorphous PET (A), the chain extender (B), and the polyester resin (C) are melt-kneaded without preparing a master batch, the chain extender (B) will react locally, and as a result, the kneaded product will gel, and the resin composition will tend to be non-uniform.
[0058] <Resin composition> The resin composition according to one embodiment of the present invention contains the master batch and the polyester resin (C). The total content of the master batch and the polyester resin (C) in the resin composition is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, based on the total mass of the resin composition. The upper limit of the total content of the master batch and the polyester resin (C) in the resin composition is not particularly limited, and may be, for example, 100% by mass, based on the total mass of the resin composition. Therefore, the total content of the master batch and the polyester resin (C) in the resin composition may be 99% by mass or more and 100% by mass or less, based on the total mass of the resin composition.
[0059] The polyester resin (C) is as described in the explanation of the masterbatch. From the viewpoint of enhancing the effect of the masterbatch, the polyester resin (C) preferably contains the following polyester resin. That is, the polyester resin (C) preferably contains at least one selected from the group consisting of crystalline polyethylene terephthalate, crystalline polytrimethylene terephthalate, crystalline polybutylene terephthalate, crystalline polycyclohexylene dimethylene terephthalate, crystalline polylactic acid, crystalline polyethylene terephthalate-isophthalate, and crystalline polycarbonate. The polyester resin (C) preferably contains recycled polyethylene terephthalate. Furthermore, the polyester resin (C) preferably contains polyethylene terephthalate having an intrinsic viscosity of 0.4 dL / g or more and 1.3 dL / g or less, measured after melt-kneading alone.
[0060] The mixing ratio of the master batch and the polyester resin (C) is preferably such that the content of the master batch is 0.1% by mass or more and 30% by mass or less with respect to the total mass of the master batch and the polyester resin (C). When the content of the master batch is 0.1% by mass or more, the moldability of the resin composition is easily improved. On the other hand, when the content of the master batch is 30% by mass or less, the content of the amorphous PET (A) in the resin composition is suppressed, and mechanical properties such as impact resistance are easily maintained. In addition, when the content of the chain extender (B) in the resin composition is suppressed, the above-mentioned crosslinking points become an appropriate amount, so that cloudiness is suppressed and a resin composition with good transparency is easily obtained. From these viewpoints, the content of the master batch with respect to the total mass of the master batch and the polyester resin (C) is more preferably 0.2% by mass or more and 10% by mass or less, and even more preferably 0.5% by mass or more and 5% by mass or less.
[0061] Since the resin composition contains the master batch that satisfies the above-mentioned condition (3), the content of the chain extender (B) in the resin composition is 0.01% by mass or more and 1.0% by mass or less based on the total mass of the resin composition. In other words, the master batch and the material containing the polyester resin (C) are mixed (melt-kneaded) so that the content of the chain extender (B) in the resin composition is 0.01% by mass or more and 1.0% by mass or less.
[0062] From the viewpoint of improving the moldability of the resin composition, the content of the chain extender (B) in the resin composition is preferably 0.02% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more. On the other hand, from the viewpoint of improving the transparency of the resin composition, the content of the chain extender (B) in the resin composition is preferably 0.9% by mass or less, more preferably 0.7% by mass or less, and even more preferably 0.5% by mass or less.
[0063] The intrinsic viscosity of the resin composition is preferably 0.4 dL / g or more and 1.2 dL / g or less. A resin composition within this intrinsic viscosity range can be applied to various applications, and is used for more appropriate applications depending on the numerical value of the intrinsic viscosity. In one embodiment, when the intrinsic viscosity of the resin composition is 0.7 dL / g or more and 1.2 dL / g or less, the resin composition is preferably for bottles or sheets. When the intrinsic viscosity of the resin composition is 0.4 dL / g or more and less than 0.7 dL / g, the resin composition is preferably for films or fibers. Furthermore, when the intrinsic viscosity of the resin composition is 0.5 dL / g or more and 0.8 dL / g or less, the resin composition is preferably for injection molding. Examples of the resin composition for injection molding include eyeglass frames, cosmetic caps, and washing machine parts. By using the above-mentioned master batch, it is possible to obtain a resin composition in which the intrinsic viscosity of the polyester resin (C), which is particularly likely to decrease by recycling, is brought close to the same level of intrinsic viscosity as before recycling, and horizontal recycling is possible.
[0064] (Other Ingredients) The resin composition may contain other components as necessary in addition to the above-mentioned master batch and polyester resin (C). Examples of other components include other components that may be contained in the above-mentioned master batch. The other components contained in the resin composition may be contained in the master batch, or may be contained separately from the master batch by being mixed with the master batch and the polyester resin (C).
[0065] <Method of producing resin composition> The resin composition can be produced by melt-kneading the master batch and the polyester resin (C). During this melt-kneading, the above-mentioned other components may be added as necessary.
[0066] As a method of melt kneading when obtaining a resin composition, for example, a method of premixing a master batch and a material containing a polyester resin (C) using a mixer such as a high-speed mixer such as a Henschel mixer or a tumbler, and then melt kneading using a kneading device can be mentioned. Examples of the kneading device include a Banbury mixer, a roll, a plastograph, a single-screw extruder, a twin-screw extruder, a kneader, and a pressure kneader. The above materials are melt kneaded using a kneading device such as an extruder, and the kneaded material is extruded into a strand shape, and the kneaded material extruded into a strand shape may be processed into a pellet shape, a flake shape, or the like. As long as it can be melt kneaded, the kneading device to be used is not particularly limited, but a pressure kneader, a Banbury mixer, or a twin-screw extruder is preferably used because of its high kneading ability. In addition, when obtaining a resin molded product from the resin composition, it is preferable that the resin composition is processed as described above and has a pellet or flake shape so that the resin composition can be easily molded by a molding machine.
[0067] The temperature during melt kneading when obtaining the resin composition may be any temperature at which the polyester resin (C) melts, and is preferably 240°C or more and 300°C or less, and more preferably 260°C or more and 280°C or less. The melt kneading when obtaining the resin composition may be performed in one stage or two stages. In the two-stage melt kneading, for example, a part of the master batch and the polyester resin (C) are melt kneaded, and the kneaded product extruded in a strand shape is processed into a pellet or flake shape. Next, the remaining master batch and the polyester resin (C), as well as other components as necessary, are added to the kneaded product in the pellet or flake shape, and the kneaded product is melt kneaded again.
[0068] The resin composition of the present embodiment described above contains the above-mentioned master batch, and therefore has good processability and moldability, as well as properties such as good transparency and low yellowness. Therefore, as will be described in the embodiment of the resin molded body below, various resin molded bodies can be manufactured by selecting various appropriate molding methods. In addition, by using the resin composition, it is possible to manufacture a resin molded body with a low haze value or a resin molded body with a low yellowness, as will be described later.
[0069] <Resin molded body> The resin molded body according to one embodiment of the present invention is a molded body of the above-mentioned resin composition. The resin molded body can be produced by molding the resin composition. Examples of the molding method include extrusion molding, T-die extrusion molding, injection molding, injection blow molding, blow molding, compression molding, and melt spinning. This makes it possible to provide a resin molded body with good transparency and low yellowness as a food container, a non-food container, an injection molded product, a sheet, a film, a tape, or a fiber.
[0070] Since the resin molded product is a molded product of a resin composition containing the master batch, it is possible for the resin molded product to have a good transparency and a low yellowness. Specifically, regarding the transparency, the resin molded product preferably has a haze value as defined by JIS K7136 of 0% or more and 10% or less, more preferably 7% or less, and even more preferably 5% or less. The haze value of the resin molded product can be a value measured according to the JIS K7136 standard.
[0071] Furthermore, the resin molded product preferably has a yellowness index (YI value) as defined by JIS K7373 of less than 15, more preferably less than 10, and even more preferably less than 5. In applications involving a large number of passes (number of times treated with a kneader or extruder), yellowing is likely to progress due to repeated application of heat, but it is sufficient that the yellowness index (YI value) is less than 15. The yellowness index (YI value) of the resin molded product can be a value measured in accordance with the provisions of JIS K7373.
[0072] As described above, one embodiment of the present invention may have the following configuration. [1] A masterbatch for polyester resin, Amorphous polyethylene terephthalate (A); and a chain extender (B) having a weight average epoxy functional group number of 3 or more and 65 or less and a weight average molecular weight of 2000 or more and 30000 or less, A masterbatch that satisfies the following conditions (1) to (3). Condition (1): The content of the chain extender (B) in the master batch is 5% by mass or more and 30% by mass or less based on the total mass of the master batch. Condition (2): Intrinsic viscosity IV after melt kneading alone a The intrinsic viscosity of a resin composition sample obtained by melt-kneading a crystalline polyethylene terephthalate having a viscosity of 0.9 dL / g or more and 1.0 dL / g or less with the master batch in a ratio such that the content of the chain extender (B) is 0.4 mass % is IV b (dL / g), 0 <IV b -IV a<0.29. Condition (3): The masterbatch is mixed with the polyester resin under conditions in which the content of the chain extender (B) in a resin composition containing the masterbatch and the polyester resin is 0.01 mass % or more and 1.0 mass % or less. [2] The masterbatch according to the above item [1], wherein the amorphous polyethylene terephthalate (A) is one in which no exothermic peak due to crystallization is observed in differential scanning calorimetry when the amorphous polyethylene terephthalate (A) is melted by heating from 30°C to 300°C at a rate of 10°C / min and then solidified by cooling to 30°C at a rate of 10°C / min. [3] The masterbatch according to the above [1] or [2], wherein the chain extender (B) has an epoxy equivalent of 100 g / mol or more and 1000 g / mol or less. [4] A resin composition containing the masterbatch according to any one of the above [1] to [3] and a polyester resin (C). [5] The resin composition according to [4] above, wherein the polyester resin (C) comprises at least one selected from the group consisting of crystalline polyethylene terephthalate, crystalline polytrimethylene terephthalate, crystalline polybutylene terephthalate, crystalline polycyclohexylene dimethylene terephthalate, crystalline polylactic acid, crystalline polyethylene terephthalate-isophthalate, and crystalline polycarbonate. [6] The resin composition according to the above [4] or [5], wherein the polyester resin (C) contains recycled polyethylene terephthalate. [7] The resin composition according to any one of the above [4] to [6], wherein the polyester resin (C) comprises polyethylene terephthalate having an intrinsic viscosity of 0.4 dL / g or more and 1.3 dL / g or less after being melt-kneaded alone. [8] The intrinsic viscosity of the resin composition is 0.7 dL / g or more and 1.2 dL / g or less; The resin composition according to any one of the above [4] to [7], which is for a bottle or a sheet. [9] The intrinsic viscosity of the resin composition is 0.4 dL / g or more and less than 0.7 dL / g; The resin composition according to any one of the above [4] to [7], which is for use in a film or fiber.
[10] The intrinsic viscosity of the resin composition is 0.5 dL / g or more and 0.8 dL / g or less; The resin composition according to any one of the above [4] to [7], which is for injection molding.
[11] A resin molded product which is a molded product of the resin composition according to any one of the above [4] to
[10] .
[12] The resin molded article according to the above
[11] , having a haze value of 0% or more and 10% or less as specified in JIS K7136.
[13] The resin molded article according to the above
[11] or
[12] , which has a yellowness index (YI value) as defined in JIS K7373 of less than 15.
[14] The resin molded article according to any one of the above
[11] to
[13] , which is a food container, a non-food container, an injection molded article, a sheet, a film, a tape, or a fiber. EXAMPLES
[0073] Hereinafter, one embodiment of the present invention will be specifically described based on examples, but one embodiment of the present invention is not limited to these examples.
[0074] <Preparing materials> The materials shown below were prepared. The epoxy equivalent and weight average molecular weight of the chain extender were measured by the following method. The measured epoxy equivalent and weight average molecular weight were used to calculate the weight average number of epoxy functional groups of the chain extender by weight average molecular weight / epoxy equivalent. The intrinsic viscosity of the polyester resin (C) shown below is a value measured for a resin obtained by melt-kneading the polyester resin alone, and the measurement method will be described later.
[0075] (Measurement of epoxy equivalent) The epoxy equivalent (g / mol) of the chain extender was determined by measurement in accordance with the standard of JIS K7236.
[0076] (Measurement of weight average molecular weight) The weight average molecular weight of the chain extender was measured by GPC using the following apparatus and conditions. GPC equipment: Product name "HLC-8020" (manufactured by Tosoh Corporation) Column: Product name "TSKgel G2000HXL", "G3000HXL", "G4000GXL" (manufactured by Tosoh Corporation) Solvent: Tetrahydrofuran (THF) ·Flow rate: 1.0mL / min Sample concentration: 2g / L ·Injection volume: 100μL ·Temperature: 40℃ Detector: Model number "RI-8020" (Tosoh Corporation) Standard material: TSK standard polystyrene (manufactured by Tosoh Corporation)
[0077] (amorphous polyethylene terephthalate) A-1: Product name: EASTAR copolyester GN071 (manufactured by Eastman Chemical Company, PET-G)
[0078] (Chain extender) B-1: Trade name "Joncryl ADR4468" (BASF, "styrene / (meth)acrylate copolymer with glycidyl group", weight average epoxy functional group number 23.4, weight average molecular weight 7250, epoxy equivalent 310g / mol) B-2: Trade name "Joncryl ADR4400" (BASF, "styrene / (meth)acrylate copolymer with glycidyl group", weight average epoxy functional group number 14.6, weight average molecular weight 7100, epoxy equivalent 485g / mol) B-3: Product name "Modiper A4100" (manufactured by NOF Corporation, "styrene / (meth)acrylate copolymer with glycidyl group", weight average epoxy functional group number 171.4, weight average molecular weight 240000, epoxy equivalent 1400g / mol) B-4: Product name "Marproof G-01100" (manufactured by NOF Corporation, "styrene / (meth)acrylate copolymer with glycidyl group", weight average epoxy functional group number 70.5, weight average molecular weight 12000, epoxy equivalent 170g / mol)
[0079] (Polyester resin (C)) C-1: Product name "MA-2101M" (Unitika, crystalline PET, intrinsic viscosity 0.60 dL / g) C-2: The polyester resin C-1 was melt-kneaded in a single screw extruder (manufactured by Nippon Placon Co., Ltd., NS type 40 mm vented extruder, L / D = 30, screw diameter = 40 mm, 3-stage Darmet, compression ratio 2.0) set at a rotation speed of 60 rpm and a barrel temperature of 280°C, extruded from the nozzle in the form of a string (strand), cooled in a water tank, and cut into pellets by a pelletizer. This operation was repeated six times (crystalline PET, intrinsic viscosity 0.47 dL / g). C-3: Product name "Kuraray Pet KS710B-8S" (Kuraray, crystalline PET, intrinsic viscosity 0.96 dL / g) C-4: Product name "SKYPURA0302" (SK Chemicals, PCT, inherent viscosity 0.63dL / g) C-5: Product name "Panlite L-1250Y" (Teijin, PC, inherent viscosity 1.08 dL / g)
[0080] <Masterbatch production> (Example 1-1) 80 parts by mass of amorphous PET resin A-1 and 20 parts by mass of chain extender B-1 were mixed using a small high-speed mixer to obtain a mixture. The mixture was then melt-kneaded in a twin-screw extruder (L / D=52.5, screw diameter=30mm) set at a rotation speed of 350 rpm and a barrel temperature of 200 to 240°C, and extruded from a nozzle in the form of a string (strand). The kneaded product extruded in the form of a strand was cooled in a water tank and then cut with a pelletizer to produce a pellet-shaped master batch.
[0081] (Examples 1-2 to 1-4, Comparative Examples 1-1 to 1-6) A master batch was prepared in the same manner as in Example 1-1 above, except that the types of materials and the amounts used (unit: parts by mass) shown in the upper row of Table 1 (Tables 1-1 and 1-2) were used.
[0082] (Masterbatch processability) The processability of the master batches was evaluated according to the following evaluation criteria. A: A master batch was produced. ×: Master batch could not be produced. In Comparative Examples 1-1 and 1-6, the kneaded mixture gelled, and in Comparative Example 1-3, the kneaded mixture did not solidify, so that a master batch could not be prepared.
[0083] (Measurement of intrinsic viscosity) The intrinsic viscosity of each of the polyester resins (C) was measured for the resin obtained by melt-kneading the polyester resin alone according to the method specified in JIS K7367-5. Specifically, the polyester resin (C) was melt-kneaded in a single-screw extruder (manufactured by Nippon Placon Co., Ltd., NS-type 40 mm vented extruder, L / D=30, screw diameter=40 mm, 3-stage Darmet, compression ratio 2.0) set at a rotation speed of 60 rpm and a barrel temperature of 280°C, extruded from the nozzle in the form of a string (strand), cooled in a water tank, and cut with a pelletizer to prepare a pelletized resin. For the polyester resin C-2, the above operation was carried out six times (6-pass product) as the material. The obtained resin was dissolved in a mixed solvent of phenol and 1,1,2,2-tetrachloroethane (tetrachloroethane) in a mass ratio of 1:1, and the intrinsic viscosity of each of the polyester resins (C) was measured at 25°C using an Ostwald viscosity tube.
[0084] The master batch that was produced and the intrinsic viscosity (IV a The intrinsic viscosity IV of the "resin composition sample" under the above-mentioned condition (2) was measured using the polyester resin C-3, which is a crystalline PET having an intrinsic viscosity of 0.96 dL / g. bwas measured. Specifically, the master batch and polyester resin C-3 were dry blended in a ratio in which the chain extender content was 0.4% by mass to obtain a mixture. The mixture was then melt-kneaded in a single-screw extruder (manufactured by Nippon Placon Co., Ltd., NS-type 40 mm vented extruder, L / D=30, screw diameter=40 mm, 3-stage Darmet, compression ratio 2.0) set at a rotation speed of 60 rpm and a barrel temperature of 280° C., and extruded from the nozzle in a string (strand) shape. The kneaded product extruded in a strand shape was cooled in a water tank, and then cut with a pelletizer to prepare a pellet-shaped resin composition sample. The intrinsic viscosity IV b The lower part of Table 1 shows the IV a , IV b , IV b -IV a Indicates the value of.
[0085] TIFF0007644301000001.tif94170
[0086] TIFF0007644301000002.tif94170
[0087] <Preparation of Resin Composition> (Example 2-1) 0.125 parts by mass of the master batch (MB1) prepared in Example 1-1 and 99.875 parts by mass of polyester resin C-1 were dry blended to obtain a mixture. The mixture was then melt-kneaded in a single-screw extruder (manufactured by Nippon Placon Co., Ltd., NS-type 40 mm vented extruder, L / D=30, screw diameter=40 mm, 3-stage Darmet, compression ratio 2.0) set at a rotation speed of 60 rpm and a barrel temperature of 280° C., and extruded from a nozzle in the form of a string (strand). The kneaded product extruded in the form of a strand was cooled in a water tank and then cut with a pelletizer to produce a pellet-shaped resin composition.
[0088] <Preparation of resin molded body> The resin composition prepared in Example 2-1 was dried at 140° C. for 4 hours, and then molded into a 1 mm thick plate using an injection molding machine (NS-40 type molding machine, mold clamping force 40 t, manufactured by Nissei Plastic Industrial Co., Ltd.) under conditions of a cylinder temperature of 280° C., an injection pressure of 60 MPa, and a mold temperature of 10° C. This was used as a test piece as a resin molded body.
[0089] (Examples 2-2 to 2-12, Comparative Examples 2-1 to 2-8) A pellet-shaped resin composition and a test piece were prepared in the same manner as in Example 2-1 described above, except that the materials and amounts (unit: parts by mass) shown in the upper row of Table 2 (Tables 2-1 to 2-3) were used. In Comparative Example 2-8, a test piece was prepared using only polyester resin (C) without using a master batch. In Comparative Example 2-4, the viscosity at the time of melting was high, and the resin did not enter the mold during injection molding, and molding was not possible. In Comparative Examples 2-2 and 2-8, the viscosity at the time of melting was too low, so the resin protruded from the gap in the mold, causing burrs.
[0090] <Measurement and evaluation methods> (processability) When pellets of the resin composition were prepared using a single-screw extruder, the state of the kneaded material extruded into strands was observed to evaluate the processability of the resin composition according to the following evaluation criteria. The evaluation results are shown in the lower part of Table 2. AA: The strand was not broken within 10 minutes and processing was possible. A: The strand broke once or twice within 10 minutes, but it was still processable. B: The strand broke 3 to 5 times in 10 minutes, but it was still processable. C: Strand breaks occurred 6 or more times in 10 min.
[0091] (Moldability) The moldability of the resin composition was evaluated according to the following evaluation criteria based on the molding conditions when the resin composition was molded into test pieces using an injection molding machine. The evaluation results are shown in the lower part of Table 2. AA: Molding was possible under injection pressure conditions equivalent to those for molding polyester resin (C) alone (hereinafter referred to as "normal conditions"). A: Molding was possible by increasing the injection pressure by 5% from the normal conditions. B: Molding was possible by increasing the injection pressure conditions by more than 5% and less than 15% from the normal conditions. C: Even when the injection pressure was increased by 15% from the normal conditions, molding was not possible, or the viscosity of the melt was low, causing the resin to protrude from the gaps in the mold, resulting in burrs.
[0092] (Measurement of intrinsic viscosity of resin composition) The intrinsic viscosity (IV) of each of the pellet-shaped resin compositions prepared in Examples 2-1 to 12 and Comparative Examples 2-1 to 8 was measured in the same manner as described above in accordance with the method specified in JIS K7367-5. The results are shown in the lower part of Table 2.
[0093] (transparency) The haze value of each test piece was measured using a haze meter (manufactured by Suga Test Instruments Co., Ltd.) as specified in JIS K7136. Based on the obtained haze value, the transparency of the test piece was evaluated according to the following evaluation criteria. The results are shown in the lower part of Table 2. AA: The haze value was 0% or more and 3% or less. A: The haze value was more than 3% and 7% or less. B: The haze value was more than 7% and 10% or less. C: The haze value was more than 10%.
[0094] (yellowness) Using a spectrophotometer (product name "CM-3600A", manufactured by Konica Minolta), each test piece was measured for transmission under a D65 light source and a 10-degree visual field to determine the L * a * b * L in color space * Value, a * value, and b *The yellowness index (YI value) was calculated according to the standard of JIS K7373, and the yellowness index of the test piece was evaluated according to the following evaluation criteria. The results are shown in the lower part of Table 2. The AA:YI value was less than 5. A: The YI value was 5 or more and less than 10. B: The YI value was 10 or more and less than 15. C: The YI value was 15 or more.
[0095] TIFF0007644301000003.tif134170
[0096] TIFF0007644301000004.tif134170
[0097] TIFF0007644301000005.tif135170
[0098] (Application example 1: T-die method) The same types and amounts of master batch and polyester resin as those in Example 2-4 were used and mixed uniformly, and then extrusion molding was performed at 280°C using a Labo Plastomill (manufactured by Toyo Seiki Co., Ltd.) equipped with a T-die to produce a sheet-like evaluation sample having a thickness of about 0.5 mm and a width of 100 mm. The produced evaluation sample was pressed to produce a sheet having a thickness of about 20 μm. When the produced sheet was visually observed, it was confirmed that the sheet had good transparency and low yellowness.
[0099] (Application example 2: Blow molding method) The same types and amounts of master batch and polyester resin as those in Example 2-4 were used and mixed uniformly, and then cylindrical bottle containers with a capacity of 200 mL and a wall thickness of 1 mm were produced using a blow molding machine with a screw diameter of 40 mm heated to 280° C. When the produced bottle containers were visually observed, it was confirmed that the bottle containers had good transparency and low yellowness.
Claims
1. A masterbatch for polyester resin, comprising: Amorphous polyethylene terephthalate (A); and a chain extender (B) having a weight average epoxy functional group number of 3 or more and 65 or less and a weight average molecular weight of 2,000 or more and 30,000 or less, A masterbatch that satisfies the following conditions (1) to (3). Condition (1): The content of the chain extender (B) in the master batch is 5 mass % or more and 30 mass % or less based on the total mass of the master batch. Condition (2): Intrinsic viscosity IV after melt kneading alone a The intrinsic viscosity of a resin composition sample obtained by melt-kneading a crystalline polyethylene terephthalate having a viscosity of 0.9 dL / g or more and 1.0 dL / g or less with the master batch in a ratio such that the content of the chain extender (B) is 0.4 mass % is expressed as an IV b (dL / g), 0<IV b -IV a <0.
29. Condition (3): The masterbatch is mixed with the polyester resin under the condition that the content of the chain extender (B) in a resin composition containing the masterbatch and the polyester resin is 0.01 mass % or more and 1.0 mass % or less.
2. The masterbatch according to claim 1, wherein the amorphous polyethylene terephthalate (A) is one in which no exothermic peak due to crystallization is observed in differential scanning calorimetry when the amorphous polyethylene terephthalate (A) is melted by heating from 30° C. to 300° C. at a rate of 10° C. / min and then solidified by cooling to 30° C. at a rate of 10° C. / min.
3. The masterbatch according to claim 1, wherein the chain extender (B) has an epoxy equivalent of 100 g / mol or more and 1000 g / mol or less.
4. A resin composition comprising the masterbatch according to any one of claims 1 to 3 and a polyester resin (C).
5. The polyester resin (C) comprises at least one selected from the group consisting of crystalline polyethylene terephthalate, crystalline polytrimethylene terephthalate, crystalline polybutylene terephthalate, crystalline polycyclohexylene dimethylene terephthalate, crystalline polylactic acid, crystalline polyethylene terephthalate isophthalate, and crystalline polycarbonate. The resin composition according to claim 4.
6. The resin composition according to claim 4, wherein the polyester resin (C) contains recycled polyethylene terephthalate.
7. The resin composition according to claim 4, wherein the polyester resin (C) contains polyethylene terephthalate having an intrinsic viscosity of 0.4 dL / g or more and 1.3 dL / g or less after being melt-kneaded alone.
8. The intrinsic viscosity of the resin composition is 0.7 dL / g or more and 1.2 dL / g or less, The resin composition according to claim 4, which is for a bottle or a sheet.
9. The intrinsic viscosity of the resin composition is 0.4 dL / g or more and less than 0.7 dL / g; The resin composition according to claim 4, which is for use in a film or fiber.
10. The intrinsic viscosity of the resin composition is 0.5 dL / g or more and 0.8 dL / g or less, The resin composition according to claim 4, which is for injection molding.
11. A resin molded product which is a molded product of the resin composition according to claim 4.
12. The resin molded article according to claim 11, wherein the haze value defined in JIS K7136 is 0% or more and 10% or less.
13. The resin molded article according to claim 11, which has a yellowness index (YI value) defined in JIS K7373 of less than 15.
14. The resin molded article according to claim 11, which is a food container, a non-food container, an injection molded article, a sheet, a film, a tape, or a fiber.
Citation Information
Patent Citations
Glycidol ether master batch, preparation method thereof and preparation method of PET (Polyethylene Terephthalate) product
CN118307938A
Modifier for crystalline polyester resin and molded article using the same
JP2006045477A
Modifier for polyester resin and method for producing molded article using the same
JP2006232976A
Heat-resistant polyester orientation-molded container
JP2011195188A
Injection molded article having excellent transparency and method for producing the same
JP2012102316A